(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Pinoy Unlimited Street Foods is an establishment that serves unlimited Filipino street foods along with beverage and desserts. Pinoy Unlimited Street Food is a general partnership type of business where the capital investment shall be distributed by its four owners. The business is located at 44 Dumalay Street, Novaliches Bayan, Quezon City. Pinoy Unlimited Street Foods also provides quality services and is a hygienic place where street foods can be eaten. The business will be based on the total numbers of customers for its pricing strategy. This study utilized the descriptive method of research design and a survey questionnaire to determine the market viability of the business. It also utilized marketing, strategies, and financial aspect. It includes the 4Ps or the product, price, place, and promotion. Good quality of the product helps the business to have good relation to the customer. If the process is right, then the product guarantees the affordability of the price for the customer proposed. This business showed that only small numbers of people do not or have not yet tried to eat street foods. The proponent also tries to identify the preference of customers in terms of 4Ps. Pinoy Unlimited Street Foods uses different advertising channels to attract more customers, including social media, flyers or leaflets, and tarpaulin while considering its objective and strategies that based on the survey questionnaire results and knowledge provided by the researchers. The pricing strategy will be the production cost plus 30% mark-up plus 12% VAT. In case of pricing the proponents, estimate the amount people can take in one meal to prevent loss on income or profit through unlimited pricing. The preference of customers is constantly changing. Thus, it is best to always conduct research on how this change can affect a present business, identify the recent preferences of customers, and try to innovate the menu, adjust price, redecorate the place, polish the techniques, maintain or enhance quantity and quality for either product or service, and always only include all of that is always profitable. The workforce of Pinoy Unlimited Street Foods only involves by its owner and a few numbers of employee on its first year of operation to ensure the income to return on the next consecutive years. It is best to take an additional employee and schedule them shift by shift to ensure that the work has the highest performance.